2014
DOI: 10.1002/cb.1505
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of young adults' materialistic values

Abstract: Given the adverse effects of materialism on consumer well‐being, the present study integrates various theoretical frameworks within the life course paradigm to assess the effects of earlier‐in‐life experiences on young Greek adults' materialistic values. Findings from a sample of 285 young adults suggest that disruptive family incidents in early life affect the development of materialistic values, while peers have no discernible influence. Disruptive family settings appear to impair socio‐economic status and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 80 publications
(141 reference statements)
0
21
0
Order By: Relevance
“…Experiences of stressful times during adolescent years tend to be remembered and recalled even after several decades, according to biographic and longitudinal studies reported by Thomae and Lehr (1986), and previous consumer studies published in leading academic journals have used samples of young adults and assessed their adolescent experiences retrospectively (e.g., Baker et al, 2013;Grougiou and Moschis, 2015;Richins and Chaplin, 2015;Rindfleisch et al, 1997).…”
Section: Samplementioning
confidence: 96%
“…Experiences of stressful times during adolescent years tend to be remembered and recalled even after several decades, according to biographic and longitudinal studies reported by Thomae and Lehr (1986), and previous consumer studies published in leading academic journals have used samples of young adults and assessed their adolescent experiences retrospectively (e.g., Baker et al, 2013;Grougiou and Moschis, 2015;Richins and Chaplin, 2015;Rindfleisch et al, 1997).…”
Section: Samplementioning
confidence: 96%
“…Kasser, Ryan, Zax, and Sameroff (1995) found that 18‐year‐olds with economically disadvantaged childhoods were more likely to value financial success than those from more privileged households (see also Twenge & Kasser, 2013), and subsequent research has attempted to determine whether this relationship extends to material values as well. Results are inconsistent, with some studies showing a negative association between childhood economic resources and materialism (Chaplin, Hill, & John, 2014; Goldberg et al, 2003; Nairn, Bottomley, & Ormrod, 2010), some showing a positive association (Baker, Moschis, Benmoyal‐Bouzaglo, & dos Santos, 2013; Manchiraju & Son, 2014), and some no association (e.g., Grougiou & Moschis, 2015; Ku, Dittmar, & Banerjee, 2012; Rindfleisch, Burroughs, & Denton, 1997).…”
Section: The Development Of Materialism In Childhoodmentioning
confidence: 99%
“…In three studies the relationship was not statistically significant (Benmoyal‐Bouzaglo & Moschis, 2010; Flouri, 1999; Moore & Moschis, 1981). One study found a significant negative (rather than positive) relationship (Grougiou & Moschis, 2015). The mean correlation in the remaining four studies was .17 (Bristol & Mangleburg, 2005; Moschis & Moore, 1979; Moschis, Ong, Mathur, Yamashita, & Benmoyal‐Bouzaglo, 2011; Weaver et al, 2011).…”
Section: The Development Of Materialism In Childhoodmentioning
confidence: 99%
“…Which result in the behavior that adolescents do not have to depend on material things as a way to develop their self-esteem (Chaplin & John, 2010). An environment of the family that encourages communication and give importance to directing oneself and individual achievement become visible in promoting materialism, whereas a family communication environment that put emphasis on obedience relative to directing oneself show discouragement to the growth of materialism (Grougiou & Moschis, 2015). So following hypothesis were proposed, H4a: Communication with parents (CP) has a negative impact on materialism H4b: Communication with friends (CF) has a positive impact on materialism.…”
Section: Communicating With Family and Friendsmentioning
confidence: 99%